Neurophysiological correlates of mismatch in lexical access - Friedrich Claudia K (BMC Neuroscience, 2005)
Abstract Background In the present study neurophysiological correlates related to mismatching information in lexical access were investigated with a fragment priming paradigm. Event-related brain potentials were recorded for written words following spoken word onsets that either matched (e.g., kan – Kante [Engl. edge]), partially mismatched (e.g., kan – Konto [Engl. account]), or were unrelated (e.g., kan – Zunge [Engl. tongue]). Previous psycholinguistic research postulated the activation of multiple words in the listeners' mental lexicon which compete for recognition. Accordingly, matching words were assumed to be strongly activated competitors, which inhibit less strongly activated partially mismatching words. Results ERPs for matching and unrelated control words differed between 300 and 400 ms. Difference waves (unrelated control words – matching words) replicate a left-hemispheric P350 effect in this time window. Although smaller than for matching words, a P350 effect and behavioural facilitation was also found for partially mismatching words. Minimum norm solutions point to a left hemispheric centro-temporal source of the P350 effect in both conditions. The P350 is interpreted as a neurophysiological index for the activation of matching words in the listeners' mental lexicon. In contrast to the P350 and the behavioural responses, a brain potential ranging between 350 and 500 ms (N400) was found to be equally reduced for matching and partially mismatching words as compared to unrelated control words. This latter effect might be related to strategic mechanisms in the priming situation. Conclusion A left-hemispheric neuronal network engaged in lexical access appears to be gradually activated by matching and partially mismatching words. Results suggest that neural processing of matching words does not inhibit processing of partially mismatching words during early stages of lexical identification. Furthermore, the present results indicate that neurophysiological correlates observed in fragment priming reflect different aspects of target processing that are cumulated in behavioural responses. Particularly the left-hemispheric P350 difference potential appears to be closely related to fine-grained activation differences of modality-independent representations in the listeners' mental lexicon. This neurophysiological index might guide future studies aimed at investigating neural aspects of lexical access.